Including water quality monitoring in rural water services: why safe water requires challenging the quantity versus quality dichotomy - Nowicki, S; Koehler, J; Charles, KJ (Springer Nature, 2020)
The need to increase drinking water quality monitoring in rural sub-Saharan Africa is widely recognised. Rural water service providers (RWSPs) may be positioned to include water quality monitoring in their activities; however, it is important that water safety activities do not compromise cooperation between the RWSP, bureaucracy, and communities. Using dilemma analysis, drawing on an institutional experiment engaging 76 stakeholders, we find that conceptualising water quality versus quantity as a dichotomy delays progress on safe water. This false dichotomy makes it more difficult to deliver water safety improvements due to contrasting assumptions about the importance of quality; risks associated with not being able to act; and unclear divisions of responsibility. Monitoring water quality can be a threat to stakeholders and stakeholder cooperation; however, this may be mitigated by including supported water safety planning in the technical and institutional design of rural water projects at their conception.